A spherical porous cuprous oxide material, a preparation method and application thereof

CN117534112BActive Publication Date: 2026-10-09ANHUI NORMAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311343010.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-17
Publication Date
2026-10-09
Estimated Expiration
2043-10-17

AI Technical Summary

Technical Problem

但是该氧化亚铜材料对应的乙烯法拉第效率较低,为34.5%~43.8%

Benefits of technology

[0052]1. The preparation method of the spherical porous cuprous oxide material of the present invention mainly uses hydrated copper nitrate as raw material, which is mixed with organic solvent and water and then sprayed. Simultaneously, by modifying the device, the water mist generated by the atomizer is guided to be directly subjected to high-temperature treatment by a tube furnace or other high-temperature device. The water mist after high-temperature pyrolysis is adsorbed onto the filter paper of the collector. Finally, the filter paper with the material adsorbed is placed in a vacuum drying oven for vacuum drying, thus obtaining the spherical porous cuprous oxide material of the present invention. Although traditional H-type electrolytic cells can quickly screen for efficient catalysts, problems such as low current density and limited CO2 mass transfer process hinder its industrial application. The present invention synthesizes spherical cuprous oxide material with a loose and porous surface through a simple, rapid, safe, and controllable spray high-temperature pyrolysis method. This significantly increases the specific surface area of ​​the catalyst and improves its catalytic activity in a flow electrolytic cell, especially enabling the selective preparation of C1/C2 gaseous products by adjusting the current. At a low current of -100 mA/cm², -2 At that time, the Faraday efficiency of electrosynthesis of CO (FE) CO The accuracy reached 96.97%; at an ampere-level current of -1000mA cm⁻¹ -2 At that time, the Faraday efficiency (FE) of ethylene electrosynthesis C2H4 The figure reached 51.28%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117534112B_ABST
    Figure CN117534112B_ABST
Patent Text Reader

Abstract

The application provides a preparation method of a spherical porous cuprous oxide material, and the preparation method comprises the following steps: (1) mixing hydrated copper nitrate, water and an organic solvent, atomizing the mixture, and performing calcination on the atomized liquid under the action of suction filtration; (2) adsorbing the reaction product prepared in the step (1) to filter paper through suction filtration, and drying until the mass of the reaction product does not change any more, so that the spherical porous cuprous oxide material is prepared. The spherical porous cuprous oxide material with a loose surface is synthesized through a simple, fast, safe and controllable spray high-temperature pyrolysis method, the specific surface area of the catalyst is greatly increased, and the catalytic activity is improved, and in particular, C1 / C2 gas phase products can be selectively prepared by adjusting the size of the electric current.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials, specifically relating to a spherical porous cuprous oxide material, its preparation method, and its application. Background Technology

[0002] Using carbon capture, utilization, and storage (CCUS) technology to treat CO2 greenhouse gas emissions from fossil fuel use is an important way to achieve the "dual carbon" goal. Using CO2 as a raw material and converting it into chemical products has enormous application prospects and environmental significance.

[0003] Renewable energy-driven CO2 electrochemical reduction (CO2RR) technology can reduce CO2 into carbon-containing compounds using water as a hydrogen source without generating additional carbon emissions. This not only solves the problem of excessive CO2 emissions but also enables the direct conversion of intermittent electrical energy into chemical energy, achieving the dual goals of deep utilization of CO2 and electrochemical energy storage. This is of great significance for achieving carbon balance and optimizing energy consumption structure.

[0004] Currently, the main C1 products of CO2RR, such as CO and formic acid, can achieve selectivity of over 90%. Moreover, multi-carbon products have higher energy density and broader market demand, thus possessing greater commercial value and application potential.

[0005] However, an ideal electrocatalyst needs to produce a single product with high current efficiency at a low overpotential. Therefore, it is crucial to develop a novel catalyst structure to meet these requirements. However, there are few reports on using Cu-based catalysts solely as electrochemical reduction catalysts for the production of CO and formic acid.

[0006] CN109536991A discloses a method for preparing a loose and porous cuprous oxide material and its application in the electrocatalytic reduction of carbon dioxide. The method primarily uses cuprous iodide powder, cleaned with dilute acid and ethanol, as raw material. A complexing solution is prepared in a potassium iodide or sodium iodide solution. A certain amount of this complexing solution is then added to a strong alkaline solution according to a specific ratio to obtain a precipitate. Finally, the precipitate is washed multiple times by centrifugation with ultrapure water and acetone and dried with nitrogen to obtain a loose and porous cuprous oxide material. This invention synthesizes a clean, loose and porous cuprous oxide material through a simple, rapid, safe, and controllable alkaline hydrolysis method, increasing the specific surface area of ​​the material and improving catalytic activity. The residual oxygen lowers the activation barrier of the intermediate product coupling reaction, greatly promoting the reactivity with multi-carbon products. The overall Faradaic efficiency for the electrocatalytic reduction of carbon dioxide to multi-carbon products such as ethylene, ethanol, and n-propanol is increased to over 80%. Although this patent provides a porous cuprous oxide material, its preparation method is complex and the product has poor homogeneity.

[0007] CN115652340A discloses a silver-modified cuprous oxide electrode for the electrocatalytic reduction of CO2 and its preparation method. Using copper chloride as a precursor, sodium hydroxide as an alkaline diluent, and ascorbic acid as a reducing agent, a bulk cuprous oxide nanostructure is first obtained. Silver nitrate solution is added, and the mixture is vigorously stirred, centrifuged, washed, and vacuum dried to obtain a silver-modified cuprous oxide catalyst. Hydrophilic conductive carbon black is added to prepare a mixed ink, which is then uniformly coated onto carbon paper and dried to obtain the silver-modified cuprous oxide electrode. The prepared silver-modified cuprous oxide electrode exhibits high catalytic activity and good stability. This is because the electrode has abundant silver-copper interfaces; the presence of cuprous oxide improves the selectivity for the product ethylene, while the presence of silver improves the catalyst's stability and suppresses the generation of the competing product hydrogen. However, the ethylene Faradaic efficiency corresponding to this cuprous oxide material is relatively low, ranging from 34.5% to 43.8%.

[0008] Therefore, it is of great significance to develop electrocatalysts that can generate a single product with high current efficiency and high selectivity at low overpotentials. Summary of the Invention

[0009] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing spherical porous cuprous oxide materials, as well as the preparation method and its application.

[0010] To achieve this objective, the present invention adopts the following technical solution:

[0011] In a first aspect, the present invention provides a method for preparing a spherical porous cuprous oxide material, the method comprising the following steps:

[0012] (1) After mixing hydrated copper nitrate, water and organic solvent, the mixture is atomized and the atomized liquid is calcined under vacuum filtration.

[0013] (2) The reaction product obtained in step (1) is adsorbed onto filter paper by vacuum filtration and dried until the mass of the reaction product no longer changes, thus obtaining the spherical porous cuprous oxide material.

[0014] Preferably, the calcination in step (1) is carried out at a high temperature of 400-600℃.

[0015] Preferably, the time for the mist to pass through the tube furnace is 2-6 seconds.

[0016] The present invention describes a method for preparing spherical porous cuprous oxide material. The method primarily uses hydrated copper nitrate as a raw material, which is mixed with an organic solvent and water, and then sprayed. Simultaneously, by modifying the apparatus, the water mist generated by the atomizer is directly passed through a high-temperature device such as a tube furnace for high-temperature treatment. The water mist after high-temperature pyrolysis is adsorbed onto the filter paper in a collector. Finally, the filter paper with the material adsorbed is placed in a vacuum drying oven for vacuum drying, thus obtaining the spherical porous cuprous oxide material of the present invention. This invention synthesizes spherical cuprous oxide material with a loose and porous surface through a simple, rapid, safe, and controllable spray-based high-temperature pyrolysis method, significantly increasing the specific surface area of ​​the catalyst and improving its catalytic activity. In particular, it allows for the selective preparation of C1 / C2 gaseous products by adjusting the current. At a low current of -100 mA cm⁻¹... -2 At that time, the Faraday efficiency of electrosynthesis of CO (FE) CO The accuracy reached 96.97%; at an ampere-level current of -1A cm⁻¹ -2 At that time, the Faraday efficiency (FE) of ethylene electrosynthesis C2H4 The figure reached 51.28%.

[0017] Therefore, the preparation method described in this invention is simple to operate, easy to scale up industrially, green and environmentally friendly, has a high yield, and the obtained spherical porous cuprous oxide material has a large specific surface area and high catalytic efficiency. It can selectively prepare C1 / C2 gaseous products by controlling the current, and has broad application prospects.

[0018] The specific value in the 400-600℃ range can be 400℃, 450℃, 500℃, 550℃ or 600℃, etc.

[0019] The specific values ​​in the 40-120℃ range can be selected from 40℃, 60℃, 80℃, 100℃, or 120℃, etc.

[0020] Other specific point values ​​within the range of the above values ​​can be selected, and will not be elaborated on here.

[0021] Preferably, the mass-volume concentration of hydrated copper nitrate in the mixture in step (1) is 5-20 g / L;

[0022] The specific values ​​in the range of 5-20 g / L can be selected from 5 g / L, 7 g / L, 9 g / L, 11 g / L, 13 g / L, 15 g / L, 17 g / L, 19 g / L, or 20 g / L, etc.

[0023] Other specific point values ​​within the range of the above values ​​can be selected, and will not be elaborated on here.

[0024] Preferably, the mass-volume concentration of hydrated copper nitrate in step (1) relative to the mixture of water and organic solvent is 5-20 g / L.

[0025] When the mass-volume concentration of hydrated copper nitrate relative to the mixture of water and organic solvent is 10 g / L, the spherical porous cuprous oxide material prepared according to the present invention has higher electrocatalytic efficiency.

[0026] Preferably, the hydrated copper nitrate in step (1) is copper nitrate trihydrate.

[0027] When the hydrated copper nitrate described in this invention is copper nitrate trihydrate, the resulting spherical porous cuprous oxide material has a large specific surface area and good electrocatalytic performance.

[0028] Preferably, the organic solvent in step (1) includes ethanol and / or ethylene glycol.

[0029] Preferably, the organic solvent in step (1) is ethanol.

[0030] Preferably, the mass ratio of water to organic solvent in step (1) is (0.5-2):1.

[0031] Preferably, the mass ratio of water to organic solvent in step (1) is 1:1.

[0032] When the mass ratio of water to organic solvent is 1:1, the spherical porous cuprous oxide material prepared according to the present invention exhibits excellent electrocatalytic performance.

[0033] Preferably, after atomization in step (1), the particle size of the spherical porous cuprous oxide material in the atomizing liquid is 300-1000 nm.

[0034] Other specific point values ​​within the range of the above values ​​can be selected, and will not be elaborated on here.

[0035] Preferably, in step (1), after atomization, the particle size of the spherical porous cuprous oxide material in the atomizing liquid is 500 nm.

[0036] When the particle size of the spherical porous cuprous oxide material in the atomizing liquid of the present invention is 500 nm, the Faraday efficiency of the electrocatalytic synthesis of C1 / C2 gas phase products by the spherical porous cuprous oxide material is higher.

[0037] Preferably, the atomizing device in step (1) is a spray generator.

[0038] Preferably, the drying in step (2) includes vacuum drying at a temperature of 40-120°C.

[0039] Preferably, the vacuum drying temperature in step (2) is 60°C.

[0040] In a second aspect, the present invention provides a spherical porous cuprous oxide material, wherein the method for preparing the spherical porous cuprous oxide includes the method for preparing the spherical porous cuprous oxide material as described in the first aspect.

[0041] This invention provides a spherical porous cuprous oxide material, the preparation method of which includes the preparation method described in the first aspect. The spherical porous cuprous oxide material is a spherical cuprous oxide material with a loose and porous surface, high specific surface area, high porosity, and low density, and can selectively prepare C1 / C2 gaseous products by adjusting the magnitude of the current.

[0042] Thirdly, the present invention provides a cuprous oxide electrocatalytic material, the cuprous oxide electrocatalytic material comprising the spherical porous cuprous oxide material and carbon paper as described in the second aspect.

[0043] The spherical porous cuprous oxide material of the present invention is attached to a carbon paper carrier and can be used as an electrode to electrocatalytically reduce CO2 to synthesize C1 / C2 products, such as CO or C2H4.

[0044] Preferably, the diameter of the spherical porous cuprous oxide material is 300-600 nm;

[0045] The specific values ​​in the 300-600nm range can be selected from 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, or 600nm, etc.

[0046] Other specific point values ​​within the range of the above values ​​can be selected, and will not be elaborated on here.

[0047] Preferably, the diameter of the spherical porous cuprous oxide material is 400 nm.

[0048] Preferably, the carbon paper is 28BC hydrophobic paper.

[0049] Preferably, the method for preparing the cuprous oxide electrocatalytic material includes: cleaning and drying the carbon paper used as the carrier of the electrocatalytic material; dissolving the spherical porous cuprous oxide material in a mixed solution of isopropanol and water; ultrasonicating the solution and then adding Nafion aqueous solution; continuing ultrasonication; pouring the ultrasonically dispersed solution into a spray gun and spraying it onto the carbon paper to obtain the cuprous oxide electrocatalytic material.

[0050] Fourthly, the present invention provides the application of the method for preparing spherical porous cuprous oxide materials as described in the first aspect in the preparation of electrocatalytic carbon dioxide reduction catalysts.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] 1. The preparation method of the spherical porous cuprous oxide material of the present invention mainly uses hydrated copper nitrate as raw material, which is mixed with organic solvent and water and then sprayed. Simultaneously, by modifying the device, the water mist generated by the atomizer is guided to be directly subjected to high-temperature treatment by a tube furnace or other high-temperature device. The water mist after high-temperature pyrolysis is adsorbed onto the filter paper of the collector. Finally, the filter paper with the material adsorbed is placed in a vacuum drying oven for vacuum drying, thus obtaining the spherical porous cuprous oxide material of the present invention. Although traditional H-type electrolytic cells can quickly screen for efficient catalysts, problems such as low current density and limited CO2 mass transfer process hinder its industrial application. The present invention synthesizes spherical cuprous oxide material with a loose and porous surface through a simple, rapid, safe, and controllable spray high-temperature pyrolysis method. This significantly increases the specific surface area of ​​the catalyst and improves its catalytic activity in a flow electrolytic cell, especially enabling the selective preparation of C1 / C2 gaseous products by adjusting the current. At a low current of -100 mA / cm², -2 At that time, the Faraday efficiency of electrosynthesis of CO (FE) CO The accuracy reached 96.97%; at an ampere-level current of -1000mA cm⁻¹ -2 At that time, the Faraday efficiency (FE) of ethylene electrosynthesis C2H4 The figure reached 51.28%.

[0053] 2. This invention provides a spherical porous cuprous oxide material, the preparation method of which includes the preparation method described in the first aspect. Cu-based catalysts can catalyze CO2 to produce complex and diverse hydrocarbons, resulting in poor selectivity for single products. The spherical porous cuprous oxide material of this invention is a spherical cuprous oxide material with a loose and porous surface, high specific surface area, high porosity, and low density. Furthermore, by adjusting the magnitude of the current, it can selectively prepare C1 and C2 gaseous products, which has certain reference value in industrial production.

[0054] 3. The spherical porous cuprous oxide material described in this invention, attached to a carbon paper carrier, can serve as an electrode for the electrocatalytic reduction of CO2 to synthesize C1 and C2 products, such as CO or C2H4. The spray-firing high-temperature pyrolysis method described in this invention is a novel process for preparing cuprous oxide. Furthermore, the catalyst prepared by this process exhibits higher current density, improved local CO2 concentration, and better mass transfer efficiency, demonstrating significant potential for industrial applications. Attached Figure Description

[0055] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0056] Figure 1 Here is a scanning electron microscope image from Application Example 1;

[0057] Figure 2 The XRD results are shown in Example 1.

[0058] Figure 3 Example 1 shows the Faraday efficiency diagram for electrocatalytic testing of CO and C2H4.

[0059] Figure 4 The scanning electron microscope image is from Application Example 2;

[0060] Figure 5 Example 2 shows the Faraday efficiency diagram for electrocatalytic testing of CO and C2H4.

[0061] Figure 6 The scanning electron microscope image is shown in Example 3.

[0062] Figure 7 Example 3 shows the Faraday efficiency diagram for electrocatalytic testing of CO and C2H4.

[0063] Figure 8 The scanning electron microscope image is shown in Example 4.

[0064] Figure 9 Example 4 shows the Faraday efficiency plots for electrocatalytic testing of CO and C2H4.

[0065] Figure 10 The scanning electron microscope image is shown in Example 5.

[0066] Figure 11 Example 5 shows the Faraday efficiency diagram for electrocatalytic testing of CO and C2H4.

[0067] Figure 12 This is a scanning electron microscope image of Comparative Example 1;

[0068] Figure 13 The XRD results are shown in Example 1.

[0069] Figure 14 For comparative example 1, the Faraday efficiency diagram of electrocatalytic testing of CO and C2H4 is shown.

[0070] Figure 15 This is a scanning electron microscope image of Comparative Example 2;

[0071] Figure 16 For comparative example 2, the Faraday efficiency diagrams for electrocatalytic testing of CO and C2H4 are shown.

[0072] Figure 17 Here is a scanning electron microscope image of Comparative Example 3;

[0073] Figure 18 The Faraday efficiency diagram for electrocatalytic testing of CO and C2H4 is shown in Comparative Example 3. Detailed Implementation

[0074] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0075] The processes, conditions, reagents, and experimental methods used in implementing this invention, except as specifically mentioned below, are all common knowledge and general knowledge in the field, and this invention does not have any particular limitations. Experimental methods in the embodiments that do not specify specific conditions are generally performed under conventional conditions or as recommended by the manufacturer.

[0076] Unless otherwise stated, all technical terms and scientific terms used in this specification have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. However, in the event of any conflict, the specification containing the definitions shall prevail.

[0077] Copper nitrate trihydrate (Cu(NO3)2·3H2O, 99.0%), potassium hydroxide (NaOH, 99.0%), ethanol (99.7%), and isopropanol (AR, 99.9%) were all purchased from Shanghai Guoyao Chemical Reagent Co., Ltd. 5% Nafion aqueous solution and Nafion 117 proton exchange membrane were purchased from DuPont. Deionized water was used to prepare all solutions in the experiment. The flow electrolysis cell apparatus was purchased from Gaoshi Ruilian. The nebulizer used in this invention was a medical ultrasonic nebulizer (1.7MHz, 35W), the circulating water vacuum pump was (Mingjie Instruments SHB-III), and the tube furnace (heating zone approximately 70cm) was used. Hydrophobic carbon paper was purchased from SGL Carbon.

[0078] Example 1

[0079] This embodiment provides a spherical porous cuprous oxide material, and the preparation method of the spherical porous cuprous oxide material is as follows:

[0080] (1) Dissolve 1g Cu(NO3)2·3H2O in 50mL H2O. After the copper salt is completely dissolved, add 50mL ethanol to the mixed aqueous solution and continue stirring until the mixture is homogeneous.

[0081] (2) The well-stirred mixture is poured into an atomizer for atomization. The atomized liquid is then guided through a 500℃ tubular furnace for 3-5 seconds using a circulating water vacuum pump. This allows the water mist, after high-temperature pyrolysis, to be adsorbed onto the filter paper in the collector under the suction of the vacuum filtration. Finally, the filter paper with the reaction product attached is placed in a 60℃ vacuum drying oven and dried for 5 hours until the mass of the reaction product no longer changes, thus obtaining the spherical porous cuprous oxide material (SEM image of the obtained material is shown below). Figure 1 As shown in the figure, the XRD results are as follows: Figure 2 (As shown).

[0082] The reaction time of the atomized liquid in the tube furnace is controlled at around 4 seconds. However, those skilled in the art will understand that due to control errors or perceived operational errors, this time control may not be precise and may fluctuate within a suitable range, such as 3-5 seconds.

[0083] Example 2

[0084] This embodiment provides a spherical porous cuprous oxide material, and the preparation method of the spherical porous cuprous oxide material is as follows:

[0085] (1) Dissolve 0.5g Cu(NO3)2·3H2O in 50mL H2O. After the copper salt is completely dissolved, add 50mL ethanol to the mixed aqueous solution and continue stirring until the mixture is homogeneous.

[0086] (2) The well-stirred mixture is poured into an atomizer for atomization. The atomized liquid is then guided through a 500℃ tubular furnace for 3-5 seconds using a circulating water vacuum pump. This allows the water mist, after high-temperature pyrolysis, to be adsorbed onto the filter paper in the collector under the suction of the vacuum filter. Finally, the filter paper with the reaction product attached is placed in a 60℃ vacuum drying oven and dried for 5 hours until the mass of the reaction product no longer changes, thus obtaining the spherical porous cuprous oxide material (SEM image of the obtained material is shown below). Figure 4 (As shown).

[0087] Example 3

[0088] This embodiment provides a spherical porous cuprous oxide material, and the preparation method of the spherical porous cuprous oxide material is as follows:

[0089] (1) Dissolve 2g Cu(NO3)2·3H2O in 50mL H2O. After the copper salt is completely dissolved, add 50mL ethanol to the mixed aqueous solution and continue stirring until the mixture is homogeneous.

[0090] (2) The well-stirred mixture is poured into an atomizer for atomization. The atomized liquid is then guided through a 500℃ tubular furnace for 3-5 seconds using a circulating water vacuum pump. This allows the water mist, after high-temperature pyrolysis, to be adsorbed onto the filter paper in the collector under the suction of the vacuum filter. Finally, the filter paper with the reaction product attached is placed in a 60℃ vacuum drying oven and dried for 5 hours until the mass of the reaction product no longer changes, thus obtaining the spherical porous cuprous oxide material (SEM image of the obtained material is shown below). Figure 6 (As shown).

[0091] Example 4

[0092] This embodiment provides a spherical porous cuprous oxide material. The preparation method of the spherical porous cuprous oxide material differs from that of Example 1 only in that the reaction temperature in the tube furnace in step (2) is replaced with 400℃ (SEM image of the obtained material is shown in Figure 1). Figure 8 (As shown).

[0093] Example 5

[0094] This embodiment provides a spherical porous cuprous oxide material. The difference between the preparation method of the spherical porous cuprous oxide material and that of Example 1 is only that the reaction temperature in the tube furnace in step (2) is replaced with 600℃ (the SEM image of the obtained material is shown in Figure 1). Figure 10 (As shown).

[0095] Comparative Example 1

[0096] (1) Dissolve 2g Cu(NO3)2·3H2O in 100mL H2O and stir continuously until the copper salt is completely dissolved;

[0097] (2) The well-stirred mixture is poured into an atomizer for atomization. The atomized liquid is guided through a 500℃ tube furnace for 3-5 seconds by vacuum filtration, so that the water mist after high-temperature pyrolysis is adsorbed onto the filter paper of the collector under the suction of vacuum filtration. Finally, the filter paper with the reaction product attached is placed in a 60℃ vacuum drying oven for 5 hours to dry completely until the mass of the reaction product no longer changes, thus obtaining the spherical porous cuprous oxide material (the SEM results of the obtained material are shown in the figure). Figure 12 As shown in the figure, the XRD results are as follows: Figure 13 (As shown).

[0098] Comparative Example 2

[0099] This comparative example provides a cuprous oxide material, which is a cubic cuprous oxide synthesized by a one-pot hydrothermal method. The preparation process is as follows: 100 mL of CuCl₂·2H₂O aqueous solution is heated to 55°C and stirred in a water bath. Then, 10 mL of NaOH aqueous solution (2M) is added dropwise to the above solution. After stirring for 30 minutes, 10 mL of ascorbic acid solution (0.6M) is added dropwise to the dark brown solution. The mixture is aged for 3 hours, and the solution gradually turns into a turbid red color. The precipitate is collected by centrifugation and washed three times with distilled water and three times with anhydrous ethanol. The precipitate is then vacuum dried at 60°C for 6 hours to obtain the cuprous oxide material (SEM image of the obtained material is shown below). Figure 14 (As shown).

[0100] (Refer to journal literature: Cu2O Nanoparticles with Both{100}and{111}Facets forEnhancing the Selectivity andActivity ofCO2 Electroreduction to Ethylene)

[0101] Comparative Example 3

[0102] This comparative example provides a simple hydrothermal synthesis method for spherical cuprous oxide materials. The preparation process is as follows: At room temperature, 3.375 g of PVP (MW 10000) and 1.125 g of Cu(CH3COO)2·H2O are dissolved in 51.5 mL of H2O and stirred at room temperature for 2 h until completely dissolved. 2.250 g of NaCl aqueous solution (10 mg / g) is then added to the mixture. -1 Subsequently, 2.5 mL of ascorbic acid solution (2.5 M) was rapidly poured into the above solution, and the mixture was stirred at 200 rpm for 5 minutes. After the reaction, the suspension was centrifuged (3000 rpm, 3 minutes) and washed twice with distilled water. The suspension was then vacuum dried at 60 °C for 5 hours to obtain spherical cuprous oxide material (SEM images of the obtained material are shown below). Figure 16 (As shown).

[0103] (Refer to journal literature: Superhydrophobic and Conductive Wire Membrane for Enhanced CO2 Electroreduction to Multicarbon Products)

[0104] The cuprous oxide materials prepared in Examples 1-5 and Comparative Examples 1-3 were used to prepare cuprous oxide electrocatalysts. The preparation method of the cuprous oxide electrocatalysts is as follows:

[0105] (1) The 28BC hydrophobic carbon paper, which serves as the carrier for the electrocatalytic material, was cleaned and dried, and then cut into 1.2×2.5cm pieces. 2 A rectangle of a certain size.

[0106] (2) Weigh 5 mg of the spherical porous cuprous oxide material prepared in Examples 1-4 and Comparative Examples 1-3, dissolve it in 500 μL of isopropanol / water (3:1) mixture, sonicate for 30 min, add 25 μL of 5% Nafion aqueous solution, and continue sonicating for 30 min. Pour the ultrasonically dispersed solution into a spray gun and spray it onto the cut carbon paper to obtain the cuprous oxide electrocatalytic material.

[0107] Test Example 1

[0108] This test example demonstrates the Faraday efficiency of the catalysts prepared using Examples 1-5 and Comparative Examples 1-3. Carbon dioxide electroreduction experiments were conducted in a flow cell. A three-electrode system consisting of a working electrode, an Ag / AgCl reference electrode, and a counter electrode (platinum sheet electrode) was used. A 1.0 M KOH aqueous solution (pH 13.5) was used as the anode and cathode electrolyte. The electrolyte flow rate was controlled at 10 rpm using a peristaltic pump. The carbon dioxide flow rate was 100 sccm, controlled by a mass flow controller. The potential was controlled by an electrochemical workstation (CHI 660D) without iR compensation. Gas chromatography (GC) was used to analyze the gaseous products generated during the electrocatalytic reduction of CO2 at each fixed potential. The test results are shown in the table below:

[0109] Table 1

[0110]

[0111] As shown in Table 1 above, the porous cuprous oxide synthesized by this process exhibits a certain potential dependence on the gaseous products CO and C2H4 in electrochemical carbon dioxide testing. This invention synthesizes spherical cuprous oxide materials with a loosely porous surface through a simple, rapid, safe, and controllable spray-firing high-temperature pyrolysis method. This significantly increases the specific surface area of ​​the catalyst and improves its catalytic activity in a flow electrolytic cell, particularly enabling the selective preparation of C1 / C2 gaseous products by adjusting the current. This is achieved at a low current density of -100 mA cm⁻¹. -2 At that time, the Faraday efficiency of electrosynthesis of CO (FE) CO The accuracy reached 96.97%; at a near-Ampere level current density of -900 mA / cm². -2 At that time, the Faraday efficiency (FE) of ethylene electrosynthesis C2H4 The efficiency reached 51.22%. Meanwhile, Example 1 achieved an ampere-level current density of -1 A cm⁻¹. -2 At that time, the Faraday efficiency (FE) of ethylene electrosynthesis C2H4 The figure reached 51.28%.

[0112] As can be seen from the performance graph of Application Example 1-5, the current density is -100 to -500 mA / cm². -1 At this time, CO synthesis is the main process, and the FE of CO decreases in a stepwise manner with increasing current density; the current density is -600 to -1000 mA cm⁻¹. -1At that time, the synthesis mainly focused on C2H4, and the Fe content of C2H4 showed a stepwise increasing trend. Based on the XRD patterns of Example 1 and Comparative Example 1, it can be seen that the catalyst preparation method of the present invention produces cuprous oxide nanomaterials. Furthermore, Examples 2-5 explored the optimal conditions for this process, thus still obtaining cuprous oxide catalysts. Compared to the cuprous oxide nanomaterials obtained using the process flow used in Control Group 1, the cuprous oxide nanomaterials exhibited superior performance in the electrocatalytic carbon dioxide field.

[0113] The alternating stepwise increase and decrease in the performance of carbon monoxide and ethylene during the electrocatalytic reduction of CO2 further demonstrates that the cuprous oxide electrocatalyst prepared by the method described in this invention can achieve highly selective generation of a single gaseous product by controlling the current density, showing promising application prospects and providing important reference for industrial production. The applicant declares that this invention illustrates the preparation process through the above embodiments, but the invention is not limited to the above embodiments, i.e., it does not mean that the invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials, additions of auxiliary components, and selection of specific methods, etc., all fall within the protection and disclosure scope of this invention.

[0114] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solution of the present invention, and these simple modifications all fall within the protection scope of the present invention.

[0115] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.

[0116] Furthermore, various different embodiments of the present invention can be combined in any way, as long as they do not violate the spirit of the present invention, they should also be regarded as the content disclosed by the present invention.

Claims

1. A method for preparing a spherical porous cuprous oxide material, characterized in that, Includes the following steps: (1) After mixing hydrated copper nitrate, water and organic solvent, the mixture is atomized and the atomized liquid is guided through a tube furnace for calcination reaction by vacuum filtration using a circulating water vacuum pump. (2) The water mist obtained by high-temperature pyrolysis through tube furnace reaction is adsorbed onto the filter paper of the collector under the suction of vacuum filtration and dried until the mass of the reaction product no longer changes, thus obtaining the spherical porous cuprous oxide material. The mass-volume concentration of hydrated copper nitrate in step (1) relative to the mixture of water and organic solvent is 5-20 g / L; the organic solvent in step (1) includes ethanol and / or ethylene glycol; the mass ratio of water to organic solvent is (0.5-2):1; the drying in step (2) is vacuum drying at a temperature of 40-120℃.

2. The application of the method for preparing spherical porous cuprous oxide material as described in claim 1 in the preparation of electrocatalytic carbon dioxide reduction catalysts.

Citation Information

Patent Citations

  • Preparation method for loosened porous cuprous oxide material and application of cuprous oxide in electrocatalytic reduction of carbon dioxide

    CN109536991A

  • Room temperature preparation method of spherical Cu2O porous adsorbing material

    CN103408055A

  • Device and method for preparing ultrafine powder by vertical spray pyrolysis

    CN112107873A

  • Crystal face coupling cuprous oxide and preparation method and application thereof

    CN113072092A